Quality of life of children with cystic periventricular leukomalacia - a prospective analysis with the Child Health Questionnaire-Parent Form 50 - Bernhard eResch; Anja eMühlanger; Ute eMaurer-Fellbaum; Elisabeth ePichler-Stachl; Elisabeth eResch; Berndt eUrlesberger (Frontiers Media S.A., 2016)
Objective: Cystic periventricular leukomalacia (PVL) is associated with moderate to severe physical and mental handicaps in preterm infants. We hypothesized whether or not those handicaps were associated with a poorer quality of life (QOL) of affected children and their families compared to matched controls.Patients and Methods: All children with the diagnosis PVL collected from a local database of the Division of Neonatology of the Medical University of Graz, Austria, and born between 1997 and 2008 were included in the study group. Preterm infants matched for gestational age, birth weight, year of birth, and gender without PVL served as controls. Selected perinatal data and neurological outcome were documented. The interview of the parents was conducted using the Child-Health-Questionnaire - Parent Form 50 (CHQ-PF50), German version. The CHQ-PF50 consists of 50 items divided over 11 multi-item scales and 2 single-item questions.Results: The CHQ-PF50 was answered by 21 parents of the study (26%) and 44 of the control (39%) group. Cases were diagnosed as having developmental delay, dystonia, strabismus, central visual impairment, seizures, and cerebral palsy (81 vs. 7%, p<0.001) more common than controls. Analysis of the CHQ-PF 50 revealed significantly poorer results for cases regarding physical health (physical functioning: p<0.001, physical social limitations: p<0.001, physical summary score: p<0.001). Several psychosocial categories (behavior, mental health, self-esteem) and the psychosocial summary score did not differ between groups. Only two categories (parental impact concerning time p=0,004, and family activities: p=0.026) revealed significantly poorer results in the cases as it was for the global category for health (p=0.009).Conclusion: Children with PVL had an overall poorer QOL regarding physical aspects. However, PVL was not generally associated with a poorer QOL regarding psychosocial aspects.